Asset Management Business Model for Design, Realization, and Maintenance of Fibre Reinforced Polymer Bridges - Rizal Sebastian (Advances in Civil Engineering)
This paper particularly addresses the market implementation of Fibre Reinforced Polymer (FRP) for bridges. It presents the concept of demand and supply chain innovation as being investigated within two ongoing European collaborative research projects (FP7) titled Trans-IND and PANTURA. FRP has emerged as a real alternative structural material based on various sustainability considerations, among others the reduced life-cycle cost due to less maintenance needs, longer lifetime, and easiness to repair, replace, or recycle the components. The Trans-IND research project aims to develop and demonstrate new industrialized processes to use FRP for civil infrastructure projects at a large scale. In order to be cost effective, a new value-chain strategy for the design, realization, and maintenance of FRP bridges is required to replace the fragmented supply chain and the one-off approach to a construction project. This paper focuses on the development of new business models based on asset management strategy, which covers the entire demand and supply chains. Research on new business models is supported by the insight into the market and regulatory frameworks in different EU countries. This is based on field surveys across the EU that have been carried out as a part of the Trans-IND and PANTURA collaborative research projects.